2019
DOI: 10.1111/ecc.13130
|View full text |Cite
|
Sign up to set email alerts
|

Nordic walking for women with breast cancer: A systematic review

Abstract: Nordic walking (NW) seems to be an interesting rehabilitation strategy for women with breast cancer (BC). No review article that has synthesised and summarised the existing scientific evidence about the effect of NW on BC survivors has been published so far. A systematic review was conducted aimed at identifying the characteristics and methodological quality of the studies that have analysed the effects of NW on women with BC. The critical appraisal of the randomised controlled trials (RCTs) was retrieved from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Nordic walking (NW) seems to be an interesting rehabilitation method for women with breast cancer. Sánchez-Lastra et al ( 44 ) conducted a study that analyzed the effects of NW on women with breast cancer. The results of the studies analyzed indicated that NW had a significant and positive effect on a number of breast cancer symptoms, including lymphedema, physical performance, disability, and sense of illness.…”
Section: Benefits Of Physical Activity On the Mental Health Of Oncology Patientsmentioning
confidence: 99%
“…Nordic walking (NW) seems to be an interesting rehabilitation method for women with breast cancer. Sánchez-Lastra et al ( 44 ) conducted a study that analyzed the effects of NW on women with breast cancer. The results of the studies analyzed indicated that NW had a significant and positive effect on a number of breast cancer symptoms, including lymphedema, physical performance, disability, and sense of illness.…”
Section: Benefits Of Physical Activity On the Mental Health Of Oncology Patientsmentioning
confidence: 99%
“…Nordic walking (NW) defines an aerobic physical activity in which poles support walking; it is low-cost and easy to perform and, thus, it is a safe, attractive, and interesting physical exercise for patients affected by breast cancer sequelae (44). It has been demonstrated that NW provides positive changes in BCRL symptoms, reduces extracellular fluid, the circumference of the arm, and the LYE absolute and relative volumes (27,35,45). Furthermore, NW helps in women's perception of BCRL regarding heaviness and tightness and upper limbs disability.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the importance of qualified instructors' interfaces with the physician and the patient and a learning phase of performing NW before they perform it independently. A recent systematic review concluded that a safe prescription to perform NW in women with BCRL might be three times a week exercise, up to 1 hour per session, the intensity of 70-80% maximum heart rate, and 11-14 of perceived exertion scale (Borg rate) (45). Finally, no evidence exists regarding any adverse effect caused by NW (e.g., falls, commonly described in association with chemotherapy due to toxicity and osteoporosis).…”
Section: Discussionmentioning
confidence: 99%
“…Nordic walking involves striding with the use of specially designed sticks and is a safe and relatively easy-to-learn form of fitness exercise. It is considered to be effective in patients with different chronic diseases [ 14 ], such as cardiovascular disease [ 15 ], aging [ 16 ], or women with breast cancer [ 17 ]. The movement sequences of Nordic walking make this physical activity suitable to support body posture and strengthen the muscles of the spine, shoulders, and hips [ 18 ].…”
Section: Introductionmentioning
confidence: 99%